The extent to which the topics of geometry and measurement in mathematics the Fifth scientific books match the criteria of the mathematics curriculum document (Journal of the College of Basic Education, 2023)
The current research aims to (The extent to which the topics of geometry and measurement in mathematics the Fifth scientific (biological and applied) books match the criteria of the mathematics curriculum document), The researcher followed the descriptive analytical approach , To verify this, the researcher prepared the list of standards of the mathematics curriculum document, , The research sample topics geometry and and measurement in mathematics books match , The researcher analyzed the topics of geometry and measurement The subject unit was adopted, and statistical means were used: repetitions, percentages, and Hollesti equation , The results of the research have concluded that the extent of the standards of the mathematics curriculum document in geometry and measurement topics are un accepted percent (42.7%) , The researcher recommended informed the competent committees in preparing and authoring the curricula in the Ministry of Education On the search results when reviewing and evaluating textbooks, paying attention to the criteria that you did not want and working to include it.